Evaluation of the Direct Compression Properties of Microcrystalline Cellulose Obtained from Cassava Fermentation Waste in Paracetamol Tablet Formulations (Nigerian Journal of Pharmaceutical Research, 2020)
Background: Natural materials have gained a lot of significance in the field of drug delivery because of their cost effectiveness and ready availability.Purpose: The study aimed at evaluating the direct compression property of microcrystalline cellulose from cassava fermentation waste in directly compressed paracetamol tablet formulations.Methods: Alkali delignification of the dried cassava fermentation fibres, followed by bleaching and acid depolymerisation was employed in the extraction of α-cellulose and conversion to microcrystalline cellulose (MCC). The MCC obtained and Avicel® were used at different concentrations (5.0-15 %w/w) to formulate batches of paracetamol tablets by directed compression. A comparative evaluation of the formulated paracetamol granules and tablets properties were undertaken.Results: The paracetamol granules formulated showed good flowability with Hausner’s ratios of 1.15-1.25, Carr’s indices of 13.10-20.00 % and angles of repose ≤ 34.41°. The formulated tablets showed good hardness (> 5.0 kgf) and disintegration time within 10 min. Only tablets containing 5.0 and 7.5 %w/w of the test MCC failed the BP dissolution test specification for tablets which stipulates that at least 70 % of the drug should be in solution after 30 min.Conclusion: This study has shown that the extracted MCC has direct compression ability evidenced in the mechanical strength of the formulated paracetamol tablets. The tablet properties of the formulated paracetamol tablets revealed pharmaceutically acceptable tablets though they were not comparable with Avicel® at all concentrations and the MCC may serve as an alternative local source for direct compression excipient